Online Dutch L2 learning in adult education: educators' and providers' viewpoints on needs, advantages and disadvantages. (2nd January 2018) - De Paepe, Liesbeth; Zhu, Chang; Depryck, Koen
Abstract: This study critically addresses the assumptions made by educators and providers in the field of Dutch second language (L2) acquisition about the online learning of Dutch L2. These include assumptions about advantages and disadvantages of online language learning, such as flexibility, learner autonomy, enhanced opportunities for remediation and differentiation versus disadvantages including the solitary learning mode, delayed feedback or high production costs. Even though stakeholders perceive a clear need for online Dutch L2 learning, and are aware of several advantages of online language learning, the current implementation level is still low. The perceived disadvantages might be a factor hindering the transition to online learning. A reorientation of the current provision of Dutch L2 courses is perceived as desirable, with self-directed, needs-oriented and customised learning as the key concepts. The outcomes shed light on perceptions that foster or hinder the development of online language courses for adult migrants, and could resonate with language professionals worldwide.